His father's son : Earl and Tiger Woods - Callahan, Tom. (Edinburgh : Mainstream, 2011)
From the time he entered the public consciousness as a two-year-old golf prodigy on The Mike Douglas Show, Eldrick'Tiger' Woods has often been viewed less as a human being and more as a ball-striking machine--and his carefully guarded image seemed to guarantee that it would remain that way. Even after his recent adultery scandal, the public still knows very little about the man. But one thing is certain: Earl Woods, Tiger's beloved and now deceased father, knew him better and influenced his life more than anyone. Here, journalist Tom Callahan offers a full biography of Earl Dennison Woods, the Vietnam War veteran who raised the golf phenomenon, and in turn, a full biography of Tiger Woods. With exclusive access to and interviews with Earl, Tiger, and a host of friends, family members, coaches, and veteran golf players, Callahan provides an unprecedented look into their lives and their remarkably close relationship. --From publisher description.
Includes index.
Keywords: Woods, Tiger; Woods, Earl, -- 1932-2006.; Golfers -- United States -- Biography; Fathers and sons -- United States